One-year outcomes and predictive factors for primary patency after stent placement for treatment of central venous occlusive disease in hemodialysis patients. (February 2022) - Chen, Bin; Lin, Run; Dai, Haitao; Yang, Jianyong; Tang, Keyu; Li, Nan; Huang, Yonghui
Objective: The study purpose was to determine the outcomes and factors predictive of primary stent patency for the treatment of central venous occlusive disease (CVOD) in hemodialysis patients. Methods: Data of 71 patients with CVOD treated with stent placement from January 2012 to December 2017 were analyzed. Univariate and multivariate analysis was performed to determine factors associated with stent patency. Adverse events related to stent placement were also examined. Results: The median primary patency duration of the 71 patients was 16 ± 2.2 months. The cumulative 3-, 6-, 9-, and 12- month primary patency rates were 93%, 72%, 55%, and 51%, respectively. Independent predictors of longer primary patency were vessel diameter > 12 mm, the use of a covered stent, and absence of vessel calcifications. Median primary patency of covered stents was 21 months as compared with only 10 months for bare stents ( p < 0.001). Procedure-related adverse events occurred in 17 patients (21.8%), and four events (5.1%) required medical intervention. No life-threaten complications occurred. Conclusions: A vessel diameter > 12 mm, the use of a covered stent, and no vessel calcifications are independently associated with a higher primary patency rate after treatment of CVOD in hemodialysis patients.